2012
DOI: 10.1051/limn/2012028
|View full text |Cite
|
Sign up to set email alerts
|

Is smaller necessarily better? Effects of small-scale forest harvesting on stream ecosystems

Abstract: -Knowledge on ecological impacts of forestry practices on aquatic ecosystems relies almost exclusively on data from large-scale forest harvesting, often involving clearfelling of whole stream catchments. To determine effects associated with less intensive and widespread forest management, we examined the responses of headwater streams to small-scale forest harvesting, including riparian zones adjacent to study reaches but corresponding to less than 5% of the catchment areas. Stream reaches running through rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 28 publications
(46 reference statements)
1
28
0
Order By: Relevance
“…Increased riparian canopy openness from blowdown increased light levels and algal biomass in streams, creating effects similar to riparian harvesting (Lecerf et al. ) and decreased buffer width (Wilkerson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased riparian canopy openness from blowdown increased light levels and algal biomass in streams, creating effects similar to riparian harvesting (Lecerf et al. ) and decreased buffer width (Wilkerson et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Litter breakdown rate did not respond consistently to the difference in the forest canopy, and thus, water temperature may not be the main explanation for differences between streams. Our findings are consistent with those of two previous studies which indicated that, in this study region, the rate of breakdown of alder in riffles may vary nonlinearly with riparian canopy cover (Lagrue et al ., ; Lecerf et al ., ). The strong coupling between litter breakdown rate and shredder density (Table ) suggests that invertebrates were directly involved in determining the variation in litter breakdown rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite compelling evidence that salmonids are affected by forest management, little is known on the genuine importance of trophic factors in mediating individual‐ and population‐level responses of fish to changes in riparian canopy cover (Mellina & Hinch ; Lecerf et al . ).…”
Section: Introductionmentioning
confidence: 97%